Acetylation of lignin containing microfibrillated cellulose and its reinforcing effect for polylactic acid. (5th July 2020) - Yetiş, Ferhat; Liu, Xuqing; Sampson, William W.; Gong, R. Hugh
Graphical abstract: Highlights: High lignin containing MFLC was isolated from CTMP without pre-treatment. The surface of MFLC was acetylated to improve the interface with PLA matrix. Ac-MFLC significantly improved the crystallization rate of PLA. Biocomposites exhibited superior mechanical performance and thermal properties. Abstract: High hemicellulose and lignin content MFC (MFLC) was isolated from chemi-thermomechanical pulp (CTMP), and surface acetylation used to significantly decrease its polarity. This modification of MFLC provided good dispersibility in PLA when used for biocomposites fabrication via a solvent casting method. MFLC exhibited higher modification efficiency compared to lignin-free MFC. Base-catalysed surface acetylation unchanged the crystalline structure of MFLC. Detection of the hydrogen bond between acetylated MFLC (Ac-MFLC) and PLA confirmed its role in improvement of the mechanical performance, thermal properties and crystallinity of the biocomposite with Ac-MFLC acting as an effective reinforcing and nucleating agent. The approach confirms the suitability of surface functionalization of MFLC for fabrication of biocomposites for a wide range of applications such as packaging and biomedical products.